PERKEMBANGAN PENDIDIKAN ISLAM DI SPANYOL - Adawiyah, Robiatul (EDUKASI: Jurnal Pendidikan Islam, 2015)
Islamic presence in Spain has brought tremendous change, especially in social and science and culture. The development of Spanish civilization Islam is formed not just by the touch of the tradition of Arab-Islamic culture multicultural society is what ultimately bound together and form a high Islamic culture at that time. The development of science is also not out of tolerance and friendship offered Islam to the indigenous population that is resident Andalusia or Spain. Traversed a long history of Muslims in Spain it can be divided into six periods, but in this paper is defined only up to the third period, this period lasts from government Abd al-Rahman III title "An-Nasir" until the emergence of al-Mulk Tawaif (kings of the group). Development of Education in Spain, In order to disseminate knowledge further, Caliph Abd-ar-Rahman III tried pioneered by founding the University of Cordova as a center of science. The university is taking place in a mosque. Based on the literature that discusses the history of education and history of Islamic civilization outline of Islamic education in Spain is divided in two sections or levels, namely kuttab and higher education.